Designing Contracts for Reducing Emissions from Deforestation and Forest Degradation - Cordero Salas, Paula (World Bank, Washington, DC, 2013)
Reduction of carbon emissions from deforestation and forest degradation has been identified as a cost effective element of the post-Kyoto strategy to achieve long-term climate objectives. Its success depends primarily on the design and implementation of a financial mechanism that provides land-holders sufficient incentives to participate in such scheme. This paper proposes self-enforcing contracts (relational contracts) as a potential solution for the constraints in formal contract enforcement derived from the stylized facts of the implementation because relational contracting relies upon mutual private self-enforcement in a repeated transaction framework. The paper derives an opportunity cost function for land use and characterizes the optimal self-enforcing contract as well as provide the parameters under which private enforcement is sustainable. The optimal payment scheme suggests that all payments should be made contingent on the carbon offsets delivered, that is, at the end of the contracting period. Thus, the optimal contract does not observe any ex ante payment. Self-enforcement is more difficult to sustain the higher the opportunity cost of forest conservation is relative to the value of the carbon offsets from the contract. Necessary extensions to the relational contracting model are also discussed.